P12.02.A Landscape of surfaceome and endocytome in human glioma is divergent and depends on cellular spatial organization. (5th September 2022) - Governa, V; Talbot, H; Gonçalves de Oliveira, K; Cerezo-Magaña, M; Bång-Rudenstam, A; Forsberg-Nilsson, K; Malmström, J; Bengzon, J; Welinder, C; Belting, M
Abstract: Background: Cell-surface proteins have a key role in drug development, and tumor cell-surface proteins integrated with the plasma membrane (tumor surfaceome, TS) have attracted considerable attention as targets for immunotherapies in cancer. Checkpoint inhibitor blocking antibodies, antibody drug conjugates (ADCs), and CAR-T cells are all directed at the TS. However, a remaining challenge is the lack of strategies to comprehensively map potential TS target antigens for the design of more rational, individualized treatments. Of particular relevance, ADC and other intracellular drug delivery strategies rely on targets that functionally engage in endocytic internalization. Material and Methods: With the aim to address these challenges and to provide insight into the complexity of the TS, we have developed a versatile technology for TS mapping (TS-MAP). As proof-of-concept, we focused on primary brain tumors that remain among the most aggressive forms of cancer, and for which attempts to conquer the most common variant, glioblastoma (GBM) have failed so far. TS-MAP is compatible with primary 3D cultures and intact patient glioma tumors with preserved tissue architecture, and specifically identifies proteins capable of endocytosis as tractable targets for ADCs and other modalities requiring toxic payload internalization. Moreover, we have curated a TS classifier (SURFME) for categorization of bona fide membrane proteins. Results: We show how cellular spatial organization (2D vs. 3D) fundamentally transforms the surfaceome and endocytome in glioma with general implications for target screening approaches. The TS-MAP platform was further applied to profile the surfaceome and endocytome landscape in a cohort of freshly resected patient gliomas. We found a highly diverse TS repertoire between patient tumors, not directly associated with grade and histology, which highlights the need for individualized approaches. Conclusions: The TS-MAP platform and SURFME classifier should be widely applicable to a variety of brain tumors. Our findings in GBM provide new layers of understanding fundamental to the future development of immunotherapy strategies, as well as new procedures for proteomics-based target identification aimed at a better understanding of how to harness the TS for personalized immunotherapy. Our results reflect the oncogenetic multiclonality and transcriptional diversity of gliomas, which warrants future studies that elucidate how the oncogenetic profile and spatial organization synergize to shape the full complexity of the tumor microenvironment.